Understanding the dominant discourse of colonialism: A qualitative, single case study of an eighth-grade U.S. History classroom. Issue 3 (4th May 2019) - Masta, Stephanie; Rosa, Tori J. K.
Abstract: The purpose of this qualitative, single case study is to investigate how teacher-created curricula addresses key Native American events in early U.S. history and to determine if such curricula provided students with accurate representations of Native American content. To do this, we used discourse analysis to consider the meanings of words and phrases, as well as the underlying assumptions and intentions of the teacher-created curricula and the experiences it claims to represent. Given the presence and use of dominant narratives to preserve power systems, curricula that deconstructs the colonizing narrative and historical representation of Native Americans can encourage the active destruction of such narratives. By analyzing four teacher-created narratives, we found is that even when a teacher creates content with the intent to be more historically accurate, the curricula still reflects a dominant narrative that privileges White settlers over Native Americans. We then provide suggestions for teachers who wish to design more culturally relevant and appropriate curricula on Native American content.